1998
DOI: 10.1161/01.str.29.10.2080
|View full text |Cite
|
Sign up to set email alerts
|

The CAMCOG: A Useful Screening Instrument for Dementia in Stroke Patients

Abstract: Background and Purpose-Most mental screening tests focus on the detection of cognitive deficits compatible with Alzheimer's disease. Stroke patients who develop a dementia syndrome, however, constitute a more heterogeneous group with both cortical and subcortical disturbances. We assessed the diagnostic accuracy of the CAMCOG (the cognitive and self-contained part of the Cambridge Examination for Mental Disorders of the Elderly) and the Mini-Mental State Examination (MMSE) for dementia in patients with a recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 34 publications
1
60
0
4
Order By: Relevance
“…Similar results have been reported in later studies (Blessed, Black, Butler & Kay, 1991;Huppert, Brayne, Gill, Paykel & Beardsall, 1995). De-Koning et al (1998) To summarise, the CAMCOG offers a more comprehensive assessment of cognitive functioning compared to the MMSE, and it has been shown to have superior diagnostic validity for the detection of dementia. However, the trade-off for this is longer administration time.…”
Section: The Cambridge Cognitive Examination ( Camcog)supporting
confidence: 79%
“…Similar results have been reported in later studies (Blessed, Black, Butler & Kay, 1991;Huppert, Brayne, Gill, Paykel & Beardsall, 1995). De-Koning et al (1998) To summarise, the CAMCOG offers a more comprehensive assessment of cognitive functioning compared to the MMSE, and it has been shown to have superior diagnostic validity for the detection of dementia. However, the trade-off for this is longer administration time.…”
Section: The Cambridge Cognitive Examination ( Camcog)supporting
confidence: 79%
“…Studies that analyzed CAMCOG as a screening tool for VCI showed excellent sensitivity and specificity 28 . Another aspect of our results also deserves to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, acute cognitive impairment after stroke has been studied mainly with global screening instruments intended to detect dementia, e.g. the Mini-Mental State Examination [28] or the CAMCOG [29]. Whereas antidepressant treatment has been shown to reduce cognitive impairment after stroke suggesting that depression causes a great deal of cognitive impairment after stroke (the so-called Fdementia of depression_ or Fpseudo-dementia_) [30,31], our results suggest that early cognitive impairment after stroke may also predict the presence of DS in the long term.…”
Section: Discussionmentioning
confidence: 99%